A metastasis-on-a-chip approach to explore the sympathetic modulation of breast cancer bone metastasis. (January 2022) - Conceição, Francisco; Sousa, Daniela M.; Loessberg-Zahl, Joshua; Vollertsen, Anke R.; Neto, Estrela; Søe, Kent; Paredes, Joana; Leferink, Anne; Lamghari, Meriem
Abstract: Organ-on-a-chip models have emerged as a powerful tool to model cancer metastasis and to decipher specific crosstalk between cancer cells and relevant regulators of this particular niche. Recently, the sympathetic nervous system (SNS) was proposed as an important modulator of breast cancer bone metastasis. However, epidemiological studies concerning the benefits of the SNS targeting drugs on breast cancer survival and recurrence remain controversial. Thus, the role of SNS signaling over bone metastatic cancer cellular processes still requires further clarification. Herein, we present a novel humanized organ-on-a-chip model recapitulating neuro-breast cancer crosstalk in a bone metastatic context. We developed and validated an innovative three-dimensional printing based multi-compartment microfluidic platform, allowing both selective and dynamic multicellular paracrine signaling between sympathetic neurons, bone tropic breast cancer cells and osteoclasts. The selective multicellular crosstalk in combination with biochemical, microscopic and proteomic profiling show that synergistic paracrine signaling from sympathetic neurons and osteoclasts increase breast cancer aggressiveness demonstrated by augmented levels of pro-inflammatory cytokines (e.g. interleukin-6 and macrophage inflammatory protein 1α). Overall, this work introduced a novel and versatile platform that could potentially be used to unravel new mechanisms involved in intracellular communication at the bone metastatic niche. Graphical abstract: The sympathetic nervous system is an important modulator of breast cancer bone metastasis. Here, a novel three-dimensional printing based, multi-compartment metastasis-on-a-chip platform with controllable diffusion directionality is described, to model the interactions on breast cancer bone metastatic niche. The multicellular crosstalk between human sympathetic neurons, breast cancer cells, and osteoclasts increases cancer cell expression of pro-inflammatory cytokines (IL-6 and MIP-1α). Image 1